Study on differentiation of tensile and Ultrasonic modulus of Highway Guardrail - Nur Khairiatun Nisa Mokhtar (Universiti Malaysia Perlis, 2009)
The aim of this study is to determine the differentiation of Young’s modulus between conventional tensile technique and ultrasonic technique. Highway guardrail used as a sample in this study was courtesy by highway concession. Sampling for tensile test were cut horizontally and vertically direction while the determination of ultrasonic modulus was carried out by TOFD probes, angle probes and goniometry immersion techniques based on ASTM 494-92 standard. Young’s modulus obtained from tensile test technique for vertical and horizontal direction samples shows no significant different. However, there were slightly different between ultrasonic modulus obtained by TOFD probes, angle probes goniometry immersion techniques. There are a huge different between tensile and ultrasonic modulus and it believed resulted by the presence of zinc that coats the mild steel in highway guardrail beam structure. On the other hand, modulus resultant by goniometry immersion technique shows the most reliable result. Thus, the ultrasonic technique for determination of highway guardrail modulus was not recommended except by using goniometry immersion technique.